NILAI SOSIAL DALAM NOVEL GADIS PANTAI KARYA PRAMOEDYA ANANTATOER - Astuti, Rr. Dwi (JURNAL PESONA, 2016)
This study aims at describing social value found in a novel, Gadis Pantai by Ananata Toer that including vital, material, and spiritual value. This study used qualitative method and content analysis. The result of study shows that this novel contains material, vital, and spiritual value. Material value is dominated by a gold, the jewelry given by Bendoro to Gadis Pantai in order to viewed as high level people. Vital value is dominated by house equipment which related to the life of Gadis Pantai and spiritual value found in her life. Based on the social value, the author asks the reader fighting for equal right at that time.Keywords: social value, novel, Gadis Pantai.